Robust tracking and distributed synchronization control of a multi-motor servomechanism with H-infinity performance. (January 2018) - Wang, Minlin; Ren, Xuemei; Chen, Qiang
Abstract: The multi-motor servomechanism (MMS) is a multi-variable, high coupling and nonlinear system, which makes the controller design challenging. In this paper, an adaptive robust H-infinity control scheme is proposed to achieve both the load tracking and multi-motor synchronization of MMS. This control scheme consists of two parts: a robust tracking controller and a distributed synchronization controller. The robust tracking controller is constructed by incorporating a neural network (NN) K-filter observer into the dynamic surface control, while the distributed synchronization controller is designed by combining the mean deviation coupling control strategy with the distributed technique. The proposed control scheme has several merits: 1) by using the mean deviation coupling synchronization control strategy, the tracking controller and the synchronization controller can be designed individually without any coupling problem; 2) the immeasurable states and unknown nonlinearities are handled by a NN K-filter observer, where the number of NN weights is largely reduced by using the minimal learning parameter technique; 3) the H-infinity performances of tracking error and synchronization error are guaranteed by introducing a robust term into the tracking controller and the synchronization controller, respectively. The stabilities of the tracking and synchronization control systems are analyzed by the Lyapunov theory. Simulation and experimental results based on a four-motor servomechanism are conducted to demonstrate the effectiveness of the proposed method. Abstract : Highlights: This paper proposes a composite control scheme which firstly addresses the coupling problem between the load tracking and the multi-motor synchronization in MMS. A NN K-filter observer is incorporated into the robust tracking controller to estimate the immeasurable states. The mean deviation coupling control is developed to achieve the multi-motor synchronization. The H ∞ performances of tracking error and synchronization error are guaranteed. Comparative experimental results reveal that the proposed control scheme outperforms the other control schemes with regarding to both transient and steady-state performance.